“A Good Name Is Better than Wealth” in Proverbs 22:1 vis-à-vis the Related Igbo Maxim “Ezi Afa Ka Ego” (Integrity Surpasses Wealth) - Odo, Damian O.; Uwaegbute, kindsley ikechukwu; Eze, Virginus U. (Old Testament Essays, 2020)
This article studies Proverbs 22:1 in relation to the Igbo maxim, ‘Ezi afa ka ego’ (Integrity surpasses wealth). The poet of Proverbs 22:1 claims that integrity surpasses wealth and then admonishes people to embrace virtues and shun vices. It is sad to observe that in the Igbo society of Nigeria, some citizens presently engage in ritual killings, human trafficking, prostitution and other vices in the quest to acquire wealth. Against this backdrop, this essay analysed Proverbs 22:1 vis-a-vis the Igbo proverb, ‘Ezi afa ka ego.’ The methodology adopted by the researchers is literary analysis, which is a synchronic approach that studies a biblical text as it appears in its final shape. The researchers employed a random sampling technique to interview seven knowledgeable Igbo people orally to examine the meaning of ‘Ezi afa ka ego’ in the Igbo context. The study affirmed that modernism has negatively affected the Igbo’s cherished value of integrity. This study charges those that engage in iniquity in order to acquire wealth to eschew such practices because a good name surpasses wealth. https://doi.org/10.17159/2312-3621/2020/v33n3a5